FAKTOR – FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI MELALUI BELANJA MODAL - Muhariyanto; Rudianti, Walid; Ghonimah Zumroatun Ainiyah (Perwira Journal of Economics & Business, 2022)
An issue that is often heard among the public in APBD management is allocating capital expenditure as an effort to increase economic growth. This research aims to examine the influence of Regional Original Income, General Allocation Funds, Special Allocation Funds on economic growth through Capital Expenditures in district/city governments in Central Java province in 2015-2019. The research data used in this research comes from secondary data. The method in this research uses a quantitative method with a saturated sample, meaning that the entire population is sampled. The population used is all districts/cities in Central Java province. The data analysis technique used is path analysis using SPSS as a statistical test tool. The research results prove that Regional Original Income directly has a significant effect on Economic Growth, while General Allocation Funds and Special Allocation Funds directly have an insignificant effect on economic growth. Capital expenditures have no direct effect on economic growth. Regional Original Income, General Allocation Funds and Special Allocation Funds have a significant effect on Capital Expenditures. Regional Original Income, General Allocation Funds and Special Allocation Funds have no effect on Economic Growth through the intervening variable Capital Expenditure. The implication of this research is that there are differences in the results of previous research and adding the capital expenditure variable as an intervening variable.